How Transformational Leadership is related to Organizational Citizenship Behavior? The Mediating Role of Emotional Intelligence (Pakistan Journal of Commerce and Social Sciences (ISSN 1997-8553), 2014)
Managers’ emotional intelligence (EI), organizational citizenship behavior (OCB) and leadership styles play an imperative role in the organizational success. The current research investigates the mediating role of EI on the relationship between OCB and transformational leadership (TL). Data has been collected from employees of banking service sector of Pakistan. SPSS and Amos have been used to test the hypotheses of study in the conceptual model. Total sample size for this study is N=300. The value for Cronbach alpha is 0.907. The results provide an evidence for the mediating effect of EI on the relationship between TL and OCB. The paper concludes with the discussion on results and implications for the academicians and manager.